(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2025)
A comprehensive thermodynamic analysis of the 500 MW Umdabaker steam power plant in Sudan was conducted, evaluating energy and exergy performance under varying thermal conditions. All major components (boiler, turbine, condenser, pumps, and feedwater heaters) were assessed through computational modeling based on thermodynamic principles. The energy analysis revealed an overall plant thermal efficiency of 37.25%, with 52.7% of total energy losses being attributed to the condenser. Through exergy analysis, the boiler was identified as the primary source of usable energy loss (205.84 MW), while the condenser’s contribution resulted in an overall exergy efficiency of only 35.8%. The impact of reference temperature variations (298.15 K to 318.15 K) was examined, showing boiler efficiency to be reduced from 43.8% to 41.1%, turbine efficiency to be slightly improved from 93.7% to 94.2%, and condenser efficiency to be dramatically decreased from 0.8% to 0.2% due to diminished temperature differentials.